Geometry of design : studies in proportion and composition - Elam, Kimberly , 1951- (Design briefs, 2011)
Using detailed diagrams and vellum overlays, explains how the science of measurement informs and creates beauty in nature and art and how we can use these techniques to create beauty in our own designs